2017
DOI: 10.1002/cpt.807
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Kidney Disease on Nonrenal Elimination Pathways: A Systematic Assessment of CYP1A2, CYP2C8, CYP2C9, CYP2C19, and OATP

Abstract: Our recent studies have shown that chronic kidney disease (CKD) affects the pharmacokinetics (PKs) of cytochrome P450 (CYP)2D6‐metabolized drugs, whereas effects were less evident on CYP3A4/5. Therefore, the effect of CKD on the disposition of CYP1A2‐metabolized, CYP2C8‐metabolized, CYP2C9‐metabolized, CYP2C19‐metabolized, and organic anion‐transporting polypeptide (OATP)‐transported drugs was investigated. We identified dedicated CKD studies with 6, 5, 6, 4, and 12 “model” substrates for CYP1A2, CYP2C8, CYP2C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(131 citation statements)
references
References 30 publications
7
123
1
Order By: Relevance
“…In our clinical study, plasma AUC of PF‐04991532 increased by ~ 2.3‐fold in the mild, moderate, and severe renal impairment subjects, compared with subjects with normal kidney function. Decrease in plasma protein binding occurs for highly bound drugs ( f u,plasma < 0.01) in kidney dysfunction, which may contribute to increasing oral clearance with severity of renal impairment . However, such effects are minimal for low protein‐bound drugs, and therefore, the likelihood of altered protein binding contributing to the PK changes of PF‐04991532 is remote ( f u,plasma 0.14).…”
Section: Discussionmentioning
confidence: 99%
“…In our clinical study, plasma AUC of PF‐04991532 increased by ~ 2.3‐fold in the mild, moderate, and severe renal impairment subjects, compared with subjects with normal kidney function. Decrease in plasma protein binding occurs for highly bound drugs ( f u,plasma < 0.01) in kidney dysfunction, which may contribute to increasing oral clearance with severity of renal impairment . However, such effects are minimal for low protein‐bound drugs, and therefore, the likelihood of altered protein binding contributing to the PK changes of PF‐04991532 is remote ( f u,plasma 0.14).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the effect of chronic kidney disease on key physiological model parameters (such as enzyme/transporter activity/abundance) is considered underdeveloped to provide reliable PBPK prediction, particularly for the severe renal impairment population, at this time. [30][31][32][33][34] Engaging With FDA Regarding PBPK-Related Submissions Early communication with the OCP is highly encouraged to promote discussions on modeling strategy, areas of uncertainty, and the types of supporting evidence needed for model development, verification, and application. Given the complexity of these models, early engagement between the sponsors and the OCP also provides the reviewers an opportunity to orient themselves to the modeling strategy that may potentially reduce the number of information requests by the OCP review team if the model is ultimately included in an NDA/BLA submission.…”
Section: Specific Populationsmentioning
confidence: 99%
“…OATP substrate drugs have been shown to have reduced clearance with increasing degree of renal failure, suggesting that the OATP function is decreased in patients with kidney disease. 5 In the current trial, we found that hemodialysis did not alter the oral clearance of fexofenadine. This indicates that reduced OATP function in patients with ESRD most likely represents either a constitutive inhibition of activity or an altered protein expression, and not an acute inhibitory effect by uremic toxins.…”
Section: Discussionmentioning
confidence: 44%
“…Increasing evidence strongly suggest that CYP-mediated drug metabolism and drug transporter function are altered in patients with ESRD. 5,6 Midazolam is considered to be the gold standard probe drug to assess CYP3A phenotype in vivo, 7 and has previously been investigated in patients with ESRD with inconclusive results. [8][9][10] Midazolam exposure was similar in patients with ESRD and healthy controls after oral dosing, 9 but significantly increased in ESRD after i.v.…”
Section: Chronic Inhibition Of Cyp3a Is Temporarily Reduced By Each Hmentioning
confidence: 99%